Cognitive Psychology of Islamic Perspective : (Critique of Modern Psychology Studies) - Moh. Toriqul Chaer; Evita Yuliatul Wahidah; Agus Salim; Achmad Rozi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
Cognitive psychology is a psychological process that involves human knowledge. Islam has a unique view of humans from the cognitive realm, which contains God's instructions about the creation of humans. The study of human nature expressed or implied and offers problem-solving for the problems of human life. This research is a qualitative study. Data was collected through the literature review of Cognitive Psychology from an Islamic perspective. The research was conduct by collecting document studies from different research results, observations and interviews. Cognitive psychology in Islam does not only focus on the brain because the thought process also includes feelings, passions, and conscience. The study of cognitive psychology from an Islamic perspective presents the method of Islamization of knowledge and an effort to explore aspects of cognitive psychology in Islam. The Islamic perspective of cognitive psychology provides an alternative to the criticism of modern psychology, which breaks away from religious values.